EFFECTS OF HEALTH EDUCATION LEARNING MANAGEMENT USING SCAFFOLDING ON LEARNING ACHIEVEMENT AND HIGHER ORDER THINKING SKILLS OF SECONDARY SCHOOL STUDENTS - Chuseechom, Peerapol; Sarayuthpitak, Jintana; Yasiersat, Chakree; Phroedphring, Chatchana (Academic Journal of Thailand National Sports University, 2022)
Purposes: To study the effects of health education learning management using scaffolding on learning achievement and higher order thinking skills of secondary school students. Methods: The subjects were 60 seventh grade students, divided equally into 30 for experimental group students who were assigned to study under the health education learning management using scaffolding while 30 students of the control group were assigned to study with the conventional teaching method. The research instruments were comprised of 8 health education lesson plans using scaffolding with IOC 0.98, as well as the data collection instruments including learning achievement in the area of knowledge, attitude, practice tests and higher order thinking skills test with IOC 0.97, 1.00, 0.89 and 0.88, and reliabilities with 0.81, 0.82, 0.81 and 0.80. The data were analyzed by mean, standard deviation and t - test. Results: The research findings are as follows: The mean scores of the learning achievement in the area of knowledge, attitude, practice and higher order thinking skills of the experimental group after learning were statistically significantly higher than that before learning at .05 level., and the mean scores of the learning achievement in the area of knowledge, attitude, practice and higher order thinking skills of the experimental group students after learning were statistically significantly higher than that the control group at .05 level. Conclusion: Health education learning management using scaffolding effects on learning achievement and higher order thinking skills of seventh grade students was higher than health education learning management with the conventional teaching method.